Plan estratégico para el mejoramiento de la administración y su desarrollo académico del sindicato de choferes profesionales del cantón Balzar, período 2014-2017”. - Vargas Moreira, Diana Carolina (2015)
At present it is important that any company or organization has a strategic plan that guided in organizational way forward. Why build it entails, as the institution does not. This work involves the development of a Strategic Plan for the improvement of the administration and its Academic level "Professional Drivers Union Balzar Canton", same that is located in the streets Juan Montalvo between Eloy Alfaro and October 4 in said Canton, Province of Guayas. Something very important in this work are the results, as they play an important role at the time of the Strategic Plan. Through technical survey found positives and negatives that have the institution, between positive can highlight the good relationship between the Directors as this is essential for development and participation depends on it having on the market. There is also the Strategic Plan in its full development highlighting important points such as the Vision, Mission Values, Policies, SWOT Institution their strategies, goals and objectives to develop in the course of its application seeking always succeed....